2016
DOI: 10.1038/mtm.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Potential for cellular stress response to hepatic factor VIII expression from AAV vector

Abstract: Hemophilia A and B are coagulation disorders resulting from the loss of functional coagulation factor VIII (FVIII) or factor IX proteins, respectively. Gene therapy for hemophilia with adeno-associated virus vectors has shown efficacy in hemophilia B patients. Although hemophilia A patients are more prevalent, the development of therapeutic adeno-associated virus vectors has been impeded by the size of the F8 cDNA and impaired secretion of FVIII protein. Further, it has been reported that over-expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
(68 reference statements)
2
49
1
Order By: Relevance
“…On the other hand, despite the initial high-level FVIII expression in hepatocyte-targeted FVIII gene therapy, a strong immune response is observed and inhibitors are developed following naked DNA transfer in HA mice (80). Moreover, it has been demonstrated that high levels of FVIII expression in hepatocytes are associated with transient endoplasmic reticulum stress and the consequent activation of unfolded protein response, with a correlation between FVIII expression and inhibitor formation (81,82).…”
Section: Gene Therapymentioning
confidence: 99%
“…On the other hand, despite the initial high-level FVIII expression in hepatocyte-targeted FVIII gene therapy, a strong immune response is observed and inhibitors are developed following naked DNA transfer in HA mice (80). Moreover, it has been demonstrated that high levels of FVIII expression in hepatocytes are associated with transient endoplasmic reticulum stress and the consequent activation of unfolded protein response, with a correlation between FVIII expression and inhibitor formation (81,82).…”
Section: Gene Therapymentioning
confidence: 99%
“…This may reflect differences in generation of long-lived plasma cells between the two species in response to FVIII, which may be harder to suppress. However, preventive tolerance induction has been accomplished in the mice using optimized expression cassettes [84, 95, 96]. High levels of FVIII expression in hepatocytes has some potential for induction of a cellular stress response, which however does not appear to increase immunogenicity [96, 97].…”
Section: Immune Tolerance Induction To the Transgene Product By LImentioning
confidence: 99%
“…However, preventive tolerance induction has been accomplished in the mice using optimized expression cassettes [84, 95, 96]. High levels of FVIII expression in hepatocytes has some potential for induction of a cellular stress response, which however does not appear to increase immunogenicity [96, 97]. An alternative method to reverse FVIII inhibitors is the combination of B cell depletion with monoclonal anti-CD20 and rapamycin, which work synergistically on the B and T cell compartments [98].…”
Section: Immune Tolerance Induction To the Transgene Product By LImentioning
confidence: 99%
“…Zolotukhin and colleagues used a codon‐optimized BDD‐FVIII within an AAV vector to transduce wild‐type C57BL/6 mice . Although there was no resultant increase in ALT levels, there was upregulation of UPR sentinel chaperone proteins at increased doses of the AAV vector.…”
Section: Challenges To Be Addressed With Bioengineered Fviii Constructsmentioning
confidence: 99%